Establishment of a novel double-antibody sandwich fluorescence microsphere immunochromatographic test strip for rapid detection of swine acute diarrhea syndrome coronavirus (SADS-CoV) infection - Xiao Cong; Xiao Cong; Fei Tong; Huizhen Liu; Huizhen Liu; Yujun Zhu; Ningxin Tan; Feng Gu; Huanan Wang; Feng Cong (Frontiers in Cellular and Infection Microbiology)
IntroductionSwine acute diarrhea syndrome coronavirus (SADS-CoV) is an enveloped, positive-sense, single-stranded RNA virus that causes clinical symptoms such as vomiting and diarrhea in 10-day-old piglets. SADS-CoV has caused significant economic losses in the swine industry in southern China. Currently, no effective treatments or vaccines are available for this disease, making it crucial to establish a point-of-care testing (POCT) technology for early diagnosis and prevention.MethodsIn this study, we first validated the specificity and immunogenicity of four monoclonal antibodies (mAbs) targeting the nucleocapsid (N) protein of swine acute diarrhea syndrome coronavirus (SADS-CoV). The optimal antibody pair for constructing the fluorescent microsphere-based immunochromatographic assay (FM-ICA) was determined through systematic pairwise screening. Critical parameters of the FM-ICA test strip, including antibody labeling concentration, coating concentration, incubation time, and sample dilution ratio, were subsequently optimized. Analytical performance characteristics of the developed FM-ICA were then rigorously evaluated. Finally, clinical validation was conducted by parallel testing of 72 field samples using both FM-ICA and quantitative PCR (qPCR), followed by concordance rate analysis.ResultsFirst, we demonstrated that all four monoclonal antibodies exhibited favorable immunogenicity and specificity. Subsequently, mAb 12E1 was identified as the coating antibody, and mAb 5G12 was selected as the labeled antibody, forming the optimal combination for FM-ICA preparation. After optimization, the ideal parameters were determined: a labeling concentration of 200 μg/mg for antibodies, a coating concentration of 1 mg/mL, an incubation time of 10 min, and a dilution factor of 10. The FM-ICA exhibited outstanding specificity, sensitivity, reproducibility, and stability, achieving a maximum detectable dilution factor of 1280 and a limit of detection (LOD) of 78 PFU mL⁻¹. Finally, the concordance rate between FM-ICA and qPCR for clinical samples reached 97.22%.DiscussionThese results indicate that FM-ICA is an excellent POCT technology that can be used for the early diagnosis of SADS-CoV, providing support for disease prevention and treatment.